Prediction of Transmembrane Regions, Cholesterol, and Ganglioside Binding Sites in Amyloid-Forming Proteins Indicate Potential for Amyloid Pore Formation - Venko, Katja; Novič, Marjana; Stoka, Veronika; Žerovnik, Eva (Frontiers in Molecular Neuroscience, 2021)
Besides amyloid fibrils, amyloid pores (AP) represent another mechanism of amyloid induced toxicity. Since 1993, many studies have confirmed that APs are formed by prefibrillar oligomers of amyloidogenic proteins and are a common source of cytotoxicity. The mechanism of pore formation is still not well understood and the structure and imaging of AP in living cells remains an open issue. To get closer to understand AP formation we used predictive methods to assess the propensity of a set of 25 amyloid-forming proteins (AFPs) to form transmembrane channels. A range of amino-acid sequence tools were applied to predict AP domains of AFPs, and provided context on future experiments that are needed in order to contribute towards a deeper understanding of amyloid toxicity. In a set of 25 AFPs we predicted their amyloidogenic propensity, presence of transmembrane (TM) regions, and cholesterol (CBM) and ganglioside binding motifs (GBM) to which the oligomers likely bind. Noteworthy, all examined APFs share the presence of TM regions, CBM and GBM motifs. For comparative purposes, we also analized a few examples of amyloid proteins that behave as non-physiological AFPs, functional amyloids and poorly characterized amyloid proteins. Based on the known experimental data on the β-amyloid and α-synuclein pore formation, we suggest that many AFPs have the potential for pore formation. Oligomerization and α-TM helix to β-TM strands transition on lipid rafts seem to be the common key events.